Mascot Design as a Visual Icon for Janti Park Tourist Attraction - Ningrum, Ninggar Mayang; Fionarizoca, Avierry; Abdurrozaq, Abdurrozaq (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to design a visual icon for Janti Park as a community-based identity for a local tourism destination. Although Janti Park has been widely recognized in the Solo Raya region, it has not yet established a consistent icon to represent its identity. The research employed a qualitative descriptive approach, involving in-depth interviews with the management of Bumdes Jaya Janti, direct field observations, and consultations with stakeholders. Academically, this research highlights the importance of community participation in visual identity design and contributes to the literature on local tourism branding. Practically, the icon serves as a branding strategy to strengthen Janti Park’s promotional efforts and ensure consistency in its visual identity. Socially, the icon reinforces community ownership of Janti Park and symbolizes appreciation for local stakeholders’ contributions.